Quality of life in adolescent and young adult cancer patients: a systematic review of the literature - Quinn, Gwendolyn P (Patient Relat Outcome Meas, 2015)
INTRODUCTION: Adolescent and young adult (AYA) cancer survivors experience many unique challenges and quality of life (QoL) effects that persist beyond cancer diagnosis and treatment. Due to continuous improvements in technology and cancer treatments resulting in improved survival rates, the identification of late effects, survivorship issues, and QoL is moving to the forefront of cancer research. The goal of this systematic review was to identify key psychosocial factors impacting QoL in AYA oncology populations. METHODS: A systematic review of the literature was conducted using combinations of these phrases or keywords: “adolescent and young adult or AYA” AND “health outcomes OR quality of life OR psychology” AND “neoplasm OR cancer OR oncology”. A total of 35 articles were included in this review. Studies were classified into two categories: AYA perceptions and stakeholder perceptions. RESULTS: AYA cancer survivors were more likely to have “worse” or impaired QoL compared with the general population, regardless of other demographic factors. AYAs described both positive and negatives experiences with their medical care, the educational information received, and the supportive care services. Although health care professionals were likely to underestimate or misjudge the health preferences and support needs of AYAs, these perceptions varied across disciplines and levels of experience. CONCLUSION: The literature is lacking in sufficient evidence-based interventions to improve QoL in AYA cancer populations. Further, the tools to adequately measure QoL in this population are also unsatisfactory. The literature, however, consistently shows agreement regarding the unique needs of this population, indicating a trend toward health care standardization within age ranges or life stages. We suggest the need for AYA-specific programs in health care institutions that comprise a multidisciplinary team that addresses all the unique medical and QoL needs of AYAs.